Digital Awareness Terhadap Toleransi Dan Penerimaan Informasi Bagi Siswa Dalam Pemanfaatan Media Sosial - Suryana, Eko; Beti , Ila Yati; Prahasti, Prahasti; Ramadani, Sabita; Alestri, Silla (Jurnal Semarak Mengabdi, 2026)
Digital awareness is a deep and comprehensive understanding of the digital world, encompassing technology, devices, the internet, and the environment and culture that shape it. It is a state in which a person is not only able to use digital technology (digital skills) but also understands the impacts, risks, ethics, and potential benefits of using that technology in everyday life. Someone with high digital awareness will act wisely, critically, and responsibly when interacting, consuming, and producing information in the digital space. This community service activity aims to provide students of SMA Muhammadiyah 4 Bengkulu with an understanding and skills to understand the importance of digital awareness in social media. Furthermore, through training and mentoring, students are provided with the opportunity to utilize the concept of digital awareness to avoid negative aspects of social media. This community service provides and demonstrates students' awareness of positive social media use and what to avoid to minimize the negative impacts resulting from carelessness. Digital awareness provides positive information on students' level of understanding and skills, encouraging them to remain aware of the influence of digital technology, which can have negative consequences if they lack a good understanding of digital awareness.